Fatigue and physical performance after a squat inertial flywheel training - De Haro, F. T. L.; Camacho, G. O.; Andrada, R. T. (Medicina dello Sport, 2021)
BACKGROUND: The aim of this study was to analyse fatigue and physical performance after performing a squat inertial flywheel training. METHODS: It was used a crossover design which included the voluntary participation of 16 trained adults (29.88±3.75 years). The participants satisfactorily completed 2 different training sessions separated by a week. One training session was performed with traditional free weights (3×15 repetitions at 70% 1RM) and the other was performed using an inertial flywheel (3×15 repetitions with inertia disc of 0.050 kg m2). The following measurements were made before and after training: vertical jump (squat jump and countermovement jump); rating of perceived exertion (RPE), perceived muscle pain and heart rate (HR). RESULTS: Significant differences were found after both training in vertical jumps, squat jump (SJ) and countermovement jump (CMJ), rating of perceived exertion, heart rate and perceived muscle pain compared to baseline. Additionally, SJ and CMJ were significantly lower after the inertial flywheel training than after the traditional training. CONCLUSIONS: The results indicate that inertial flywheel training caused significantly more fatigue and loss of performance than traditional free weight training.